ADDIE-based AI training using open-source LMS for vocational teachers - Rosyanto, Rosyanto; Wahyudin, Dinn; Hernawan, Asep Herry (Universitas Pendidikan Indonesia, 2025)
This study examines the application of the ADDIE (Analysis, Design, Development, Implementation, Evaluation) framework in developing an Artificial Intelligence (AI) training program through an open-source Learning Management System (LMS) for vocational school teachers. It addresses the lack of structured AI training and low teacher preparedness in vocational education. The objective of this study is to evaluate how each ADDIE phase contributes to improving teachers’ competencies in teaching Artificial Intelligence (AI) using an open-source LMS. A mixed-methods approach was used with 150 teachers from 15 vocational schools in West Java, Indonesia. Training was delivered through a public LMS using blended learning. Data were collected via surveys, classroom observations, and LMS analytics. Path analysis was conducted using SmartPLS to assess the relationships between ADDIE phases and training outcomes. Results revealed a notable improvement in AI literacy and an increase in instructional capabilities and teachers’ technology proficiency post-training. The Design and Implementation stages had the most substantial impact on learning outcomes. The open-source LMS proved effective and scalable for AI training. This study provides a structured approach to professional development and highlights the potential for integrating AI into vocational education, particularly in low-resource settings. AbstrakPenelitian ini mengkaji penerapan kerangka kerja ADDIE (Analysis, Design, Development, Implementation, Evaluation) dalam mengembangkan pelatihan Kecerdasan Artifisial (AI) berbasis platform Learning Management System (LMS) sumber terbuka bagi guru Sekolah Menengah Kejuruan (SMK). Penelitian ini merespons minimnya pelatihan AI yang terstruktur serta rendahnya kesiapan guru vokasi. Tujuan penelitian ini adalah mengevaluasi kontribusi setiap tahapan ADDIE terhadap peningkatan kompetensi guru vokasi dalam mengajar AI dengan memanfaatkan LMS sumber terbuka. Metode campuran digunakan, melibatkan 150 guru dari 15 SMK di Jawa Barat, Indonesia. Pelatihan diselenggarakan melalui LMS publik dengan pendekatan blended learning. Data dikumpulkan melalui survei, observasi kelas, dan analisis penggunaan LMS. Analisis jalur dilakukan menggunakan SmartPLS untuk menilai hubungan antara tahapan ADDIE dan hasil pelatihan. Hasil menunjukkan peningkatan signifikan dalam literasi AI dan kemampuan instruksional guru dalam penguasaan teknologi pasca pelatihan. Tahapan Design dan Implementation berpengaruh paling besar terhadap hasil pembelajaran. LMS sumber terbuka terbukti efektif dan dapat diskalakan untuk pelatihan AI. Penelitian ini menawarkan model pengembangan profesional yang terstruktur dan menunjukkan integrasi AI dalam pendidikan vokasi, terutama di lingkungan dengan keterbatasan sumber daya.Kata Kunci: guru sekolah menengah kejuruan; kecerdasan artifisial; LMS sumber terbuka; model ADDIE; pelatihan guru